Paleoflora del Cretácico Inferior de península Byers, islas Shetland del Sur, Antártida (Ameghiniana, 2014)
New paleofloristic findings on Byers Península, Shetland Islands, Antarctica, expand our knowledge about Mesozoic floras fram that continent. Twenty-seven taxa of hepatophytes, equisetaleans, ferns, pteridosperms, bennettitaleans, pentoxylaleans and conifers are described. The first occurrence of hepatophytes, equisetaleans, and fertile leptosporangiate ferns in the palaeoflora is documented. The flora is an important reference assemblage, beca use it is radiometrically dated as early Aptian.